2022
DOI: 10.2147/jir.s384020
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Dectin-1 Alleviates Neuroinflammatory Injury by Attenuating NLRP3 Inflammasome-Mediated Pyroptosis After Intracerebral Hemorrhage in Mice: Preliminary Study Results

Abstract: Background Neuroinflammation plays an important role following intracerebral hemorrhage (ICH). NLRP3 inflammasome-mediated pyroptosis contributes to the mechanism of neuroinflammation. It has been reported that dendritic cell-associated C-type lectin-1 (Dectin-1) activation triggers inflammation in neurological diseases. However, the role of Dectin-1 on NLRP3 inflammasome-mediated pyroptosis after ICH remains unclear. Here, we aimed to explore the effect of Dectin-1 on NLRP3 inflammasome-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“… [ 82 ] Dectin-1 Dectin-1 blockade inhibits NLRP3 activation. [ 83 ] Sennoside A It inactivates caspase-1 to inhibit NLRP3 and AIM2 inflammasome-involved inflammation. [ 84 ] Total extract of Abelmoschus manihot L Inhibition of caspase-8/caspase-3/NLRP3/GSDME signaling.…”
Section: Factors Affecting Rt-induced Pyroptosismentioning
confidence: 99%
“… [ 82 ] Dectin-1 Dectin-1 blockade inhibits NLRP3 activation. [ 83 ] Sennoside A It inactivates caspase-1 to inhibit NLRP3 and AIM2 inflammasome-involved inflammation. [ 84 ] Total extract of Abelmoschus manihot L Inhibition of caspase-8/caspase-3/NLRP3/GSDME signaling.…”
Section: Factors Affecting Rt-induced Pyroptosismentioning
confidence: 99%
“…Upon inflammatory stimulation, the NLRP3 inflammasome aggregates, resulting in the activation of Caspase-1 . Activated Caspase-1 further cleaves and activates IL-1β and IL-18, inducing neuronal pyroptosis (Ding et al, 2022).…”
Section: Classical Activation Of Microglia Leads To Neuronal Pyroptosismentioning
confidence: 99%
“…An increasing number of studies have revealed that secondary injury after cerebral hemorrhage can lead to a large amount of neuronal loss, and neuroinflammation plays a key role in this process [5,6]. Thus, inhibiting neuroinflammation has become an attractive possibility as an effective means to improve the prognosis of cerebral hemorrhage [7].…”
Section: Introductionmentioning
confidence: 99%